(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
The Italian Northern Apennines are acknowledged as the place where ichnology was born, but there is comparatively little work about their ichnological record. This study bridges this gap by describing two new ichnosites from the locality of Pierfrancesco, which preserve an abundant, low-disparity trace-fossil assemblage within the Late Cretaceous beds of the M. Cassio Flysch. Results show that lithofacies and ichnotaxa are rhythmically organized. The base of each cycle consists of Megagrapton-bearing calciclastic turbidites, which are overlain by marlstone beds with an abundant, low-disparity assemblage of trace fossils. This includes Chondrites intricatus, C. patulus, C. targionii, C. recurvus and Cladichnus fischeri. The cycle top consists of mudstones with no distinct burrows. The rhythmic pattern of Pierfrancesco reflects a deep-sea ecological succession, in which species and behaviour changed as turbidite-related disturbances altered the seafloor. This study opens the question of whether the Chondrites-Cladichnus ichnocoenosis represents low-oxygen or nutrient-poor settings.